(untitled) (International Journal of Communication Systems and Network Technologies, 2019)
The technology improves the ability of data storage and their processing. Therefore a significant growth on different business domains is observed. The business intelligence requires data and consumer habits but the requirement of data is never fulfilled by a single data source. In this context required to combine the different source of information for making smart decisions or for finding the conclusions. But the limitation is that nobody wants to disclose their client’s private and sensitive information to others. Therefore we need a privacy preserving environment to handle the data, it’s privacy and conclusion. In this presented paper privacy preserving data mining is the key area of investigation using the available literature. Additionally by concluding the literature need to establish the future prospects for the work.